2017
DOI: 10.1038/nature20788
|View full text |Cite
|
Sign up to set email alerts
|

Genomic hallmarks of localized, non-indolent prostate cancer

Abstract: Prostate tumours are highly variable in their response to therapies, but clinically available prognostic factors can explain only a fraction of this heterogeneity. Here we analysed 200 whole-genome sequences and 277 additional whole-exome sequences from localized, non-indolent prostate tumours with similar clinical risk profiles, and carried out RNA and methylation analyses in a subset. These tumours had a paucity of clinically actionable single nucleotide variants, unlike those seen in metastatic disease. Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
502
6
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 516 publications
(551 citation statements)
references
References 61 publications
25
502
6
2
Order By: Relevance
“…This is significantly higher than in primary PCa, 6/498 patients (1.2%) ( Figure 1B and Table S3) (p<0.0001 Fisher exact test). Examination of data across additional primary and metastatic prostate cancer datasets revealed a similar difference in the frequency of biallelic CDK12 mutations between primary and metastatic cancer (Table S4) (Abida et al, 2017; Beltran et al, 2016; Fraser et al, 2017; Kumar et al, 2016). CRPC genomes are more highly mutated than those of localized tumors; however, the magnitude of the increased mutation rate is not sufficient to explain the increased frequency of biallelic loss of CDK12.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…This is significantly higher than in primary PCa, 6/498 patients (1.2%) ( Figure 1B and Table S3) (p<0.0001 Fisher exact test). Examination of data across additional primary and metastatic prostate cancer datasets revealed a similar difference in the frequency of biallelic CDK12 mutations between primary and metastatic cancer (Table S4) (Abida et al, 2017; Beltran et al, 2016; Fraser et al, 2017; Kumar et al, 2016). CRPC genomes are more highly mutated than those of localized tumors; however, the magnitude of the increased mutation rate is not sufficient to explain the increased frequency of biallelic loss of CDK12.…”
Section: Resultsmentioning
confidence: 92%
“…Comprehensive genomic analyses have substantially furthered our understanding of primary prostate cancer (PCa) and metastatic castration-resistant prostate cancer (mCRPC) (Barbieri et al, 2012; Beltran et al, 2016; Fraser et al, 2017; Grasso et al, 2012; Robinson et al, 2015; The Cancer Genome Atlas Research Network, 2015). These studies have discovered common genetic drivers of prostate cancer, such as fusions of ETS genes (Tomlins et al, 2005), amplification of AR , and loss of CDKN2A , PTEN , RB1 , SPOP , and TP53 (Robinson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, mutations in mismatch repair genes involved in fixing single-strand DNA breaks ( MSH2, MLH6 ) were very rare (<1%). A second study evaluating the genomic landscape of 477 localized intermediate-risk (Gleason 6–7) prostate cancers found that 47 patients (10%) harbored DNA repair mutations in homologous recombination genes: FANCA (n=9), ATM (n=8), RAD51 (n=7), CDK12 (n=6), and BRCA2 (n=5) [13]. Therefore, the prevalence of homologous recombination mutations in primary prostate cancer is likely between 8–10%.…”
Section: Genetic Landscape Of Localized and Advanced Prostate Cancermentioning
confidence: 99%
“…A clear message as to the uniqueness of every patient's tumor from the major genetic characterization studies [32,33,34,37,38,39] raises the following questions: To what extent should we inform ourselves about the genetic alterations of every single tumor? Should we sequence every tumor's genome completely or retrieve information only about certain genes?…”
Section: Genetic/molecular Heterogeneitymentioning
confidence: 99%